Dendritic spine density is increased on nucleus accumbens D2 neurons after chronic social defeat - Megan E. Fox (Nature Portfolio, 2020)
Abstract Stress alters the structure and function of brain reward circuitry and is an important risk factor for developing depression. In the nucleus accumbens (NAc), structural and physiological plasticity of medium spiny neurons (MSNs) have been linked to increased stress-related and depression-like behaviors. NAc MSNs have opposing roles in driving stress-related behaviors that is dependent on their dopamine receptor expression. After chronic social defeat stress, NAc MSNs exhibit increased dendritic spine density. However, it remains unclear if the dendritic spine plasticity is MSN subtype specific. Here we use viral labeling to characterize dendritic spine morphology specifically in dopamine D2 receptor expressing MSNs (D2-MSNs). After chronic social defeat, D2-MSNs exhibit increased spine density that is correlated with enhanced social avoidance behavior. Together, our data indicate dendritic spine plasticity is MSN subtype specific, improving our understanding of structural plasticity after chronic stress.